An exploration of methods for rating children's productions of sibilant fricatives. (2nd January 2016) - Munson, Benjamin; Urberg Carlson, Kari
Abstract : Background : This paper examines three methods for providing ratings of within-category detail in children's productions of /s/ and /ʃ/. Method : A group of listeners ( n = 61) participated in a rating task in which a forced-choice phoneme identification task was followed by one of three measures of phoneme goodness: visual analog scaling, direct magnitude estimation, or a Likert-scale judgment. Results : All three types of ratings were similarly correlated with sounds' acoustic characteristics. Visual analog scaling and Likert-scale judgments had higher intrarater reliability than did direct magnitude estimation. Moreover, both of them elicited a wider range of judgments than did direct magnitude estimation. Conclusion : Based on our evaluation, Likert-scale judgments and visual analog scaling are equally useful tasks for eliciting within-category judgments. Of these two, visual analog scaling may be preferable because it allows for more distinct levels of response.